The association of metabolic dysfunction-associated steatotic liver disease (MASLD) with the risk of myocardial infarction: a systematic review and meta-analysis - Qiong Lv; Huashan Zhao (Annals of Medicine, 2024)
AbstractObjective While studies have documented how metabolic dysfunction-associated steatotic liver disease (MASLD) can contribute to cardiovascular disease (CVD), whether MASLD is associated with myocardial infarction (MI) remains debateable. Herein, we systematically reviewed published articles and performed a meta-analysis to determine the relationship between MASLD and MI risk.Methods PubMed, MEDLINE, Embase, Web of Science, CNKI, CBM, VIP, and WanFang databases were searched, and the DerSimonian Laird method was used to obtain hazard ratios (HRs) for binary variables to assess the correlation between MASLD and MI risk. Subgroup analyses for the study region, MASLD diagnosis, quality score, study design, and follow-up time were conducted simultaneously for the selected studies retrieved from the time of database establishment to March 2022. All study procedures were independently conducted by two investigators.Results The final analysis included seven articles, including eight prospective and two retrospective cohort studies. The MI risk was higher among MASLD patients than among non-MASLD patients (HR = 1.26; 95% CI: 1.08-1.47, p = 0.003). The results of the subgroup analysis of the study region revealed an association of MASLD with MI risk among Americans and Asians, but not in Europeans. Subgroup analyses of MASLD diagnosis showed that ultrasonography and other (fatty liver index[FLI] and computed tomography [CT)]) diagnostic methods, but not international classification of disease (ICD), increased the risk of MI. Subgroup analysis of the study design demonstrated a stronger relationship between MASLD and MI in retrospective studies but not in prospective studies. Subgroup analysis based on the follow-up duration revealed the association of MASLD with MI risk in cases with < 3 years of follow-up but not with ≥3 years of follow-up.Conclusion MASLD increases the risk of MI, independent of traditional risk factors.